Norms - Barroso, Paulo (2020)
Norms (from the Greek nómoi and the Latim norma, meaning “carpenter’s square, rule, pattern”) are socially shared rules of behavior or action expressing what one ought and ought not to do under certain circumstances. Norms are authoritative rules or standards (of right and wrong or truth and falsehood) by which someone or something is judged and, on that basis, approved or disapproved. Therefore, norms are rules, precepts, and models that govern and guide the courses of social actions. This entry provides an overview of norms in general and social norms in particular, then explores media as a factor of socialization.